The American “Civilizing Mission:” the Tuskegee Institute and its involvement in African colonialism - Smith, Kenneth (Kansas State University, 2018)
Many historians believe that the United States did not play a major role in the European colonial affairs of Africa. The “civilizing mission” in Africa was largely a European matter that the United States did not have any involvement in and instead stayed out of African affairs. However, this is in fact not true. Industrial education was a new way of managing and “civilizing” African populations after the global end of slavery and the archetype of industrial education was in Tuskegee, Alabama at the Tuskegee Institute. The Tuskegee Institute was the pinnacle of industrial education. Students came not just from the United States, but from around the world as well to learn a trade or improved technologies in agriculture. It allowed students to attend the school for free in exchange for working the farms at the school and general upkeep while training them to be better farmers and tradesmen. On the surface, it offered an avenue for blacks to carve their own economic path. Implicitly, however, it did not offer African Americans and Africans a path towards upward mobility as it continued to relegate them to menial labor jobs and worked within the confines of the established racial hierarchy in which blacks were not granted the same opportunities as whites, in this instance it was education. This thesis argues that the Tuskegee Institute’s (now Tuskegee University) method of industrial education became an influential model for managing the African colonies via industrial education and that the United States was thus more involved in the “civilizing mission” than previously thought. The Tuskegee Institute first ventured into Africa when it assisted the German Colonial Government in Togo in establishing industrial education which helped to develop infrastructure and modern technology in the colony. Second, I examine Tuskegee’s role in Liberia as it established the Booker Washington Institute which is still in existence today. Lastly, I illustrate the diverse effects of the Tuskegee Model of education in Africa and how it correlated to Tuskegee education in the United States and how events in both Africa and the United States led to the collapse of the Tuskegee Model.
Keywords: Cotton; Tuskegee; Colonialism; Africa; Industrial education; African American